OBJECTIVE FACTORS FOR ENHANCING HUMAN DIGNITY (International journal of artificial intelligence, 2026)
This article provides a scientific and practical analysis of the objective factors contributing to the enhancement of human dignity in the context of New Uzbekistan. It highlights the protection of human rights and freedoms, safeguarding citizens’ legitimate interests, and strengthening openness and transparency as priority directions of state policy. The study substantiates that presidential decrees, resolutions of the Cabinet of Ministers, institutional reforms, and the development of public oversight mechanisms have played a significant role in ensuring human dignity in practice. In addition, the article reveals the socio-legal significance of positive changes achieved in the fields of freedom of speech, freedom of conscience, and gender equality, emphasizing their impact on democratic governance and social justice.